Pengaruh Structural Empowerment, Leader Empowerment, dan Psychological Empowerment terhadap Innovative Behavior Guru di SMK XYZ Jakarta - Kurniasih, Okti (Jurnal Ketopong Pendidikan, 2023)
Innovative behavior is an important factor in improving teachers’ performance. An individual who is innovative is able to seek and discover new ways of accomplishing tasks more effectively and efficiently. However, innovation can only grow within a person if they work in an environment that supports its development. The purpose of this study is to examine the influence of structural empowerment, leader empowerment, and psychological empowerment on teachers’ innovative behavior. The subjects of this research were thirty five teachers from SMK XYZ located in South Jakarta. The research design used was correlational, employing a survey to collect data, which was then analyzed using the PLS-SEM method. The results indicate that structural empowerment, leader empowerment, and psychological empowerment have a positive influence on teachers’ innovative behavior.